Children interaction patterns exhibited during learning activities: a case study at a selected public kindergarten in Malaysia - Abd Rahim, Siti Noor Fauziah; Nik Abdul Rahman , Nik Suryani (worldconferences.net, 2013)

(untitled)
This qualitative research aims to explore the nature of children interaction patterns during their learning activities. This study involved six 6-year old children (4 boys and 2 girls) from a selected public kindergarten in Malaysia. Employing the case study design method, data was collected using non-participant observation techniques. The findings of this study revealed that there were two types of children interaction during learning activities: children-adult interaction and children-peers interaction. The patterns of children interaction in children-adults interaction comprised; constructive-dialogic and explicit correction while in children-peers interaction, children engaged in three patterns of interaction namely; sociable, creative and non-verbal. Finally, implications of this study for preschool education in particular will be discussed. Field of Research: Children, Interaction, Learning Activities, Social Constructivism, Qualitative Research.